Prior Preterm or Small-for-Gestational-Age Birth Related to Maternal Metabolic Syndrome - Catov, Janet M. (2011)
OBJECTIVE: To estimate whether women who deliver small babies due to preterm birth or growth restriction have excess risk for cardiovascular disease and diabetes later in life. METHODS: Eight years after pregnancy, we estimated the prevalence of metabolic syndrome and its components in a cohort study of women with prior preterm (preterm birth before 37 weeks, n=181) or small for gestational age ([SGA], less than the tenth percentile, n=192) births, compared with women with term births (37 or more weeks, n=306). Women delivered at Magee-Womens Hospital in Pittsburgh, Pennsylvania, and those with preeclampsia or prepregnancy diabetes or hypertension were excluded. Women underwent a structured interview and fasting blood sampling. RESULTS: Women were, on average, 8 years postpartum and 39 years old at evaluation. Women with a prior preterm birth had higher blood pressure, triglycerides, and LDL-cholesterol compared with those in a term control group. Women with prior SGA births were leaner and more likely to smoke compared with those with term births. Women with prior preterm birth had elevated risk of metabolic syndrome, adjusted for demographic, smoking and body size factors (23% preterm compared with 17% control group; odds ratio [OR] 1.76 [1.06, 2.80]). In women with a prior preterm birth, low HDL (11% preterm compared with 5% control group; OR 2.6 [1.2, 5.2]), hypertriglyceridemia (22% compared with 14%; OR 1.9 [1.2, 2.9]), and elevated glucose (24% compared with 19%; OR 1.5 [1.0, 2.3]) accounted for this excess metabolic syndrome. In women with SGA, the only element of metabolic syndrome that was aberrant was glucose metabolism. CONCLUSION: Eight years after pregnancy, women with prior preterm or SGA births had evidence of metabolic syndrome compared with women with term births. Screening and intervention in these women after pregnancy may delay or prevent disease.